2018
DOI: 10.1159/000490795
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Noninvasive Score Predicts Disease Activity and Deep Remission in Ulcerative Colitis

Abstract: Background: There is a need to use noninvasive markers in refining the management of ulcerative colitis to reduce the number of unnecessary colonoscopies, which facilitates the follow-up of activity and the response to treatment. Aim: Postulation of a sensitive, specific, simple and noninvasive score to monitor disease activity in ulcerative colitis. Methods: A case-control study was conducted: 168 patients with ulcerative colitis, 40 healthy individuals, and 60 patients for validation. Patients were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Using a newly developed “noninvasive activity score”, Hanafy et al [ 82 ] reported NLR was higher in newly diagnosed patients with UC or in relapse, compared to patients in remission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a newly developed “noninvasive activity score”, Hanafy et al [ 82 ] reported NLR was higher in newly diagnosed patients with UC or in relapse, compared to patients in remission.…”
Section: Resultsmentioning
confidence: 99%
“…UC: NLR was assessed to potentially differentiate patients with active UC from patients with inactive UC in the following studies: Hanafy et al [ 82 ]—cutpoint at 2.35 (74.0% sensitivity, 86.0% specificity) Demir et al [ 62 ]—cutpoint at 2.39 (48.6% sensitivity, 77.5% specificity) Chen et al (2020) [ 37 ]—cutpoint at 2.40 (76.2% sensitivity, 84.5% specificity) Celikbilek et al [ 60 ]—cutpoint at 2.47 (53.9% sensitivity, 63.2% specificity) Acarturk et al [ 35 ]—cutpoint at 3.1 (78.0% sensitivity, 69.0% specificity, p < 0.001) Zhang et al (2017) [ 56 ]—cutpoint at 3.29 (47.4% sensitivity, 93.9% specificity) Dong et al [ 63 ]—cutpoint at 4.70 (61.0% sensitivity, 86.0% specificity) …”
Section: Resultsmentioning
confidence: 99%
“…However, based upon the disease severity this change in the BMI could be insigni cant. As reported by Hanafy et al (2018) who reported that the mean values of the body mass index for the IBD and controls (11).…”
Section: Discussionmentioning
confidence: 63%
“…Blood samples for the measurement of high-sensitivity C-reactive protein (CRP) were taken 1 week prior to or after endoscopy. CRP was measured using a nephelometric method (18). In brief, human CRP reacted with the corresponding antisera in the liquid phase to generate antigen-antibody complexes and produce turbidity using a CRP immunoturbidimetric assay kit [DiaSys Diagnostic Systems (Shanghai) Co., Ltd., Shanghai, China] according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The turbidity was associated with the antigen content and the CRP content in the sample was calculated by comparing the samples with PBS using Detection system 1 Hitachi 7600-020 automatic biochemical analyzer (Hitachi, Ltd., Tokyo, Japan). In healthy people, blood CRP levels are <5 mg/l (18). To avoid bias, all gastroenterologists performing the endoscopies were unaware of the results from the disease activity index.…”
Section: Methodsmentioning
confidence: 99%